Оценки устойчивых предельных циклов нелинейных дискретных систем - Кунцевич, А.В.; Кунцевич, В.М. (Проблемы управления и информатики, 2012)
Визначено умови існування інваріантних множин (стійких граничних циклів) для досить широкого сімейства автономних нелінійних дискретних систем. Запропоновано методи визначення оцінок зверху граничних циклів. Наведено ілюстративні приклади. Основну увагу в роботі приділено визначенню радіуса оцінки граничного циклу, оскільки саме він визначає найбільше відхилення системи від початку координат при русі системи по граничному циклу. We define the existence conditions for invariant sets (stable limit cycles) of a considerably wide family of autonomous nonlinear discrete systems. We present the methods of calculating the upper-bound estimates for the limit cycles and illustrate application of these methods with examples. The main focus is given to calculation of the radius of a set estimate for the limit cycle, since it determines the maximum deviation from the origin while moving over the limit cycle.